Poling forces during roller skiing: effects of grade - Millet, G. Y.; Hoffmann, M. D.; Candau, R. B.; Clifford, P. S. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: A substantial proportion of the propulsive forces required for uphill skiing are generated from the upper body, but no study has systematically examined poling forces at different slopes. In the present experiment, poling forces and timing were examined during roller skiing on 2.1% and 5.1% uphills. METHODS: Nine highly skilled cross-country skiers roller skied at paced submaximal and at maximal speeds using the V1 skate (V1) and double pole (DP) techniques. Poling forces and timing were measured with piezoelectric transducers. RESULTS: Peak force (PF), average force (AF) and average force over the entire cycle (ACF) were significantly greater (P < 0.01) at the steeper grade with both techniques. Values for the ratio of V1 to DP did not differ between the two grades for PF, AF, and ACF but tended to increase with velocity for both techniques. With both V1 and DP, upper body recovery time was shorter (P < 0.01) at the steeper grade, and cycle rate was greater (P < 0.01) at the steeper grade. CONCLUSIONS: We conclude that 1) the relative demands on the upper body with V1 compared with DP were similar between the two grades, and 2) the responses to an elevation in grade of increased poling forces, shortened poling recovery times, and increased cycle rate are comparable to the responses to an increase in speed.